2019
DOI: 10.1128/jcm.00573-19
|View full text |Cite
|
Sign up to set email alerts
|

Genomics for Molecular Epidemiology and Detecting Transmission of Carbapenemase-Producing Enterobacterales in Victoria, Australia, 2012 to 2016

Abstract: Carbapenemase-producing Enterobacterales (CPE) are being increasingly reported in Australia, and integrated clinical and genomic surveillance is critical to effectively manage this threat. We sought to systematically characterize CPE in Victoria, Australia, from 2012 to 2016. Suspected CPE were referred to the state public health laboratory in Victoria, Australia, from 2012 to 2016 and examined using phenotypic, multiplex PCR and whole-genome sequencing (WGS) methods and compared with epidemiological metadata.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 43 publications
3
62
0
Order By: Relevance
“…Note: carbapenemase-producing Enterobacterales excluded as already covered by existing state-wide genomic surveillance program [5]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note: carbapenemase-producing Enterobacterales excluded as already covered by existing state-wide genomic surveillance program [5]. …”
Section: Methodsmentioning
confidence: 99%
“…Clinical and screening isolates of six MDROs were collected from hospital inpatients: vanA vancomycin-resistant Enterococcus faecium ( vanA VRE), methicillin-resistant Staphylococcus aureus , extended-spectrum beta-lactamase (ESBL)-phenotype Escherichia coli and Klebsiella pneumoniae (ESBL-Ec and ESBL-Kp), carbapenem-resistant Acinetobacter baumannii complex (CRAb) and carbapenem-resistant Pseudomonas aeruginosa (CRPa)(Table 2). Carbapenem-resistant Enterobacterales (CPE) were excluded, as these were already collected for a comprehensive state-wide CPE surveillance program [5, 27]. Whilst vanB VRE are dominant in Australia, we elected to focus on vanA VRE as it emerged more recently in Victoria, has a greater level of associated antimicrobial resistance and costs, and could potentially be more amenable to infection control interventions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data were used to identify clusters of isolates for which the genomes differed by ≤ 100 and ≤ 25 single nucleotide variants (SNVs). Isolates from the same facility and separated by ≤ 25 SNVs can be considered putative nosocomial transmission clusters [67,69,70]; distances ≤ 100 SNVs also imply descent from a recent common ancestor, but are more consistent with community or between-facility transmission, or regional spread between countries [70].…”
Section: Genome Assembly and Genotypingmentioning
confidence: 99%
“…The authors concluded that there was strong geographic structuring of strains, and that the expansion of a handful of clonal lineages was predominantly responsible for the spread of carbapenemases in K. pneumoniae in Europe, with onward nosocomial transmission. Like bla KPC-3 in EuSCAPE, bla KPC-2 has also been linked with the clonal expansion of ST258 in Australia(26), where 48% of 176 K. pneumoniae isolates sequenced were bla KPC-2 -containing ST258.…”
Section: Discussionmentioning
confidence: 99%